DEVELOPING STUDENTS’ DILIGENCE AND CREATIVITY THROUGH THE INTEGRATION OF TECHNOLOGY AND VISUAL ARTS SUBJECTS - Safoyeva Kamola Qudrat qizi (The Conference Hub, 2025)
In the era of globalization and technological advancement, education must prepare students for a world that demands innovation, perseverance, and creative problem-solving. Traditional subject-based teaching often isolates disciplines, preventing learners from perceiving knowledge as interconnected. Integrating technology and visual arts provides a bridge between analytical and imaginative thinking, helping students link knowledge with real-life application.According to Dewey (1938), learning is most effective when students engage in experiences that combine doing and thinking. Integrating technological processes with artistic creativity embodies this principle by engaging students cognitively, emotionally, and practically. Such integration helps develop responsibility, attention to detail, and persistence, alongside imagination and aesthetic awareness.